“What does Ferguson mean for the food justice movement?”: Reading Black visions of food justice in times of social unrest - Smith II, Bobby; Walida Simon, Jamila; Star Gwin, Candace; McMillion, Desirée (Journal of Agriculture, Food Systems, and Community Development, 2024)
The August 2014 murder of unarmed Black teenager Michael Brown at the hands of the police in the streets of Ferguson, Missouri, USA, sparked international attention, ignited a surge in #BlackLivesMatter protests, and reconfigured national discussions about race, police brutality, and state-sanctioned violence. Black food activists on the frontlines of the food justice movement grappled with Brown’s murder by joining together on a national call to address the question: What does Ferguson mean for the food justice movement? Answers to this question manifested into the 2015–2016 special digital series entitled “What Ferguson Means for the Food Justice Movement,” published online in the Food Justice Voices section of the WhyHunger organization website. In this article, we use a qualitative critical content analysis of the series to examine how Black food activists reframed agricultural and food systems in the context of the Ferguson struggle. We draw on intersectional agriculture theory to illuminate how Black food activists draft visions of food justice through three intersecting pathways: (1) critical Black agrarianism, (2) radical Black mothering, and (3) Black futures. Our research reveals that Black visions of food justice in the wake of Ferguson are instructive and offer a fresh lens to understand the evolving landscape of Black food activism, given a set of racial, gendered, social, political, and economic realities. We conclude with a brief discussion on how these visions compel us to reconsider racial equity at the nexus of agriculture, food, and various forms of unrest in Black communities, providing insights for scholars, practitioners, and activists who work on issues of food justice.